Study of goat rearing systems and their impact on young goat production in the Sahelian zone of Africa: The case of West Mayo-Kebbi, Chad - NAJJAR, AMEL; ZAHIIKY, KYEBLOUABÉ SIGNABOUBO; ZEUH, VOUNPARET; GASMI-BOUBAKER, AZIZA; KHALDI, SANA (The Indian Journal of Animal Sciences, 2024)
The present study was conducted in the province of West Mayo Kebbi–Chad, and involved 96 goat farmers covering 3599 animals belonging to the local breed. Production performances of kids raised for butchery were estimated based on their kidding mode (simple, double, or triple), their mortality rate, and their age at weaning. Present findings showed the pinpointing of two main goats rearing systems: the traditional extensive (TE=24%) and the semi-extensive systems (SE=76%), with a higher number of goats reared in the SE compared to the TE systems. Feeding is based on grazing at 90% and 100% for SE and TE, respectively. Supplementation is practiced in the SE system, using hay and agricultural by-products. Most of the kidding was recorded during the dry season, with a comparable average annual number of live kids produced per farm for the SE and TE systems. Similarly, the average annual kid’s neonatal mortality per farm did not vary between the SE and TE systems. The simple, double, and triple kidding mode was higher in the SE system compared to the TE system, yet the age at weaning was similar in both systems. Besides, the study also showed that the most goat farmers belong to the SE farming system. Their feeding practices are almost the same in both farming systems except for supplementation, which is usually practiced in the SE. Conclusively, the production performances did not vary between the two farming systems, except for the kidding mode, which was higher in the SE farming system.